FAKTOR – FAKTOR KETERLAMBATAN PROYEK KONSTRUKSI DI KABUPATEN MERAUKE PAPUA BERDASARKAN STUDI KASUS DI INDONESIA - Anggara Hutahaen; Arief Setiawan Budi Nugroho; Muslikh (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2022)
The increasingly high development in Indonesia has spurred the number of construction service companies to increase. On the other hand, the increase in the growth of construction service companies has not been accompanied by a good atmosphere of construction implementation. As a result, delays in completing work have become commonplace in construction projects in Indonesia, the eastern part, and especially Papua. This research investigated the factors causing delays in completing construction work in Papua Province, especially in Merauke Regency. Questionnaires were distributed to contractors registered as members of GAPEKSINDO and domiciled in the Merauke district. The purposive sampling technique took the number of samples. The data analysis in this research used a Non-Parametric Statistical Test with Kendall's W analysis using SPSS 25.0 for the Windows program. The seven main factors that cause construction project delays are related to consultants. The test results show that the main factor of delay in construction projects in the Merauke Regency is the labor factor, with a mean rank value of 2.56. Factors that do not affect construction delays are other factors with a mean rank value of 5.28.